The Winterhouse mysteries - Guterson, Ben (Guterson, Ben. Winterhouse, 2021)
Danger, intrigue, and the power of family combine in The Winterhouse Mysteries, the fast-paced conclusion to Ben Guterson and Chloe Bristol's illustrated, enchanting Winterhouse middle grade trilogy. It's springtime at Winterhouse and Elizabeth is settling into the joyful chaos of her new home. But it isn't long before she and Freddy are drawn into an ominous new mystery. Guests at the hotel start behaving oddly, and Elizabeth's powers manifest in thrilling--sometimes frightening--new ways. As unnatural tremors shake the foundations of Winterhouse, Elizabeth hears cries for help from Gracella Winters, a villain she'd thought dead and gone for good. Elizabeth's discovery of a rare book containing secrets of an ancient ritual leads to a tragic realization: someone at the hotel is trying to help Gracella rise again. Can Elizabeth and Freddy banish these threats and protect the future of Winterhouse once and for all? Christy Ottaviano Books.